The Positive Influence of Creating a Holistic Facial Composite on Video Line‐up Identification. Issue 5 (13th June 2014) - Davis, Josh P.; Gibson, Stuart; Solomon, Chris
Summary Witnesses to a crime may be asked to create a facial composite of the offender from memory. They may then view a suspect in a police line‐up. Previous research on this topic has found both recognition impairment and enhancement following composite construction. In Experiment 1, creator‐participants employed the holistic facial composite system system EFIT‐V or the feature‐based E‐FIT system to create a single composite, and in Experiment 2, creators constructed up to three EFIT‐Vs. In both experiments, facial composite creators were one‐and‐a‐half times more likely than non‐composite creating controls to make correct target identifications from a video line‐up. No between condition effects were found in target‐absent trials in Experiment 1. The development of holistic facial composite systems has enhanced suspect identification rates in police investigations, and these results suggest that the use of such a system can also have a positive influence on a composite‐creating witness' later recognition of the suspect. Copyright © 2014 John Wiley & Sons, Ltd.